Analisis Implementasi Kebijakan Program Percepatan Penurunan Stunting Terintegrasi Di Kabupaten Sidoarjo - Muharram, Fajar; Cholifah, Siti; Utami, Purnama Julia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the implementation of the Integrated Stunting Reduction Acceleration Program policy in Sidoarjo Regency using a qualitative descriptive approach. The research employs Policy Implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The qualitative research method used is descriptive, with data collected through interviews, observations, and documentation. The findings reveal that policy communication has been effectively conducted, although significant challenges remain at the village level, particularly regarding public understanding and participation. Human and non-human resources are considered adequate; however, their distribution remains uneven and requires improvement to achieve optimal effectiveness. The implementers' disposition shows a high level of commitment to the program, but transparency in policy implementation remains a challenge to be addressed. The bureaucratic structure has supported coordination among stakeholders, although some procedures are perceived as overly complex and need simplification to improve implementation efficiency. The implementation of the Integrated Stunting Reduction Acceleration Program in Sidoarjo Regency reflects the local government's strong commitment to addressing nutritional challenges through a holistic approach. This program targets a reduction in the stunting rate to 14% by 2024, employing various measures such as the Bangga Kencana Consolidation, Convergence of Stunting Reduction Acceleration, and intensive public awareness campaigns. Regular evaluations have shown positive results, including a significant decrease in the stunting rate from 16.1% in 2022 to 8.4% in 2023. By integrating relevant sectors and actively involving the community, this strategy has proven effective in creating an environment that supports optimal child growth. With improvements in these three aspects, the effectiveness of policy implementation is expected to increase, enabling the program to have a more significant impact on reducing stunting rates in Sidoarjo Regency.